2015
DOI: 10.1161/atvbaha.115.305631
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Levels of MMP-12 Are Associated With Atherosclerotic Burden and Symptomatic Cardiovascular Disease in Subjects With Type 2 Diabetes

Abstract: Objective— Matrix metalloproteinases (MMPs) degrade extracellular matrix proteins and play important roles in development and tissue repair. They have also been shown to have both protective and pathogenic effects in atherosclerosis, and experimental studies have suggested that MMP-12 contributes to plaque growth and destabilization. The objective of this study was to investigate the associations between circulating MMPs, atherosclerosis burden, and incidence of cardiovascular disease with a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 33 publications
9
69
1
4
Order By: Relevance
“…The same group then continued to show that plasma levels of the matrix metalloproteinases 7 and 12 were elevated in type 2 diabetics and were associated with increased incidence of atherosclerosis and cardiovascular disease. 26 …”
Section: New Mechanistic Insight Into Regulation Of Inflammation Assomentioning
confidence: 99%
“…The same group then continued to show that plasma levels of the matrix metalloproteinases 7 and 12 were elevated in type 2 diabetics and were associated with increased incidence of atherosclerosis and cardiovascular disease. 26 …”
Section: New Mechanistic Insight Into Regulation Of Inflammation Assomentioning
confidence: 99%
“…However, it may be favorable in other conditions, such as POP (24). In a recent study by Goncalves et al , it was shown that ‘high plasma levels of MMP-3 were associated with lower plaque elastin content’ (32). Therefore, a higher MMP-3 gene expression potentially decreases elastin concentrations in human body tissues, such as pelvic floor supporting structures (i.e., ligaments and fascia).…”
Section: Discussionmentioning
confidence: 99%
“…25 Consistent with the role of matrix metalloproteinases in destabilizing atherosclerotic plaques, elevated plasma levels of matrix metalloproteinase-12, which can degrade elastin, fibronectin, laminin, and type IV collagen, correlate with an increased rate of coronary events in patients with type 2 diabetes mellitus. 26 However, there are also descriptions of plasma biomarkers that correlate with a more stable fibrous plaque phenotype and a lower incidence of cardiovascular events. Rattik et al 27 describe smooth muscle cell growth factors (eg, heparin-binding epidermal growth factor) as such markers.…”
Section: Biomarkers Of Plaque Instabilitymentioning
confidence: 99%